A unifying principle for global greenness patterns and trends - Wenjia Cai; Ziqi Zhu; Sandy P. Harrison; Youngryel Ryu; Han Wang; Boya Zhou; Iain Colin Prentice (Communications Earth & Environment)
Abstract Vegetation cover regulates the exchanges of energy, water and carbon between land and atmosphere. Remotely-sensed fractional absorbed photosynthetically active radiation (fAPAR), a land-surface greenness measure, depends on carbon allocation to foliage while also controlling photon flux for photosynthesis. Here we use an equation with just two globally fitted parameters to describe annual maximum fAPAR as the smaller of a water-limited value transpiring a constant fraction of annual precipitation, and an energy-limited value maximizing annual plant growth. This minimalist description reproduces global greenness patterns and temporal trends in remote-sensing data, comparable to the best-performing dynamic global vegetation models. Widely observed greening is attributed principally to the influence of rising carbon dioxide on the light- and water-use efficiencies of photosynthesis; limited browning regions are attributed to drying. This research provides one key component of ecosystem function as a step towards more robust foundations for new-generation land ecosystem models.